Respuesta :
Solve for x:
3 sqrt(x + 8) = -4
Divide both sides by 3:
sqrt(x + 8) = -4/3
Raise both sides to the power of two:
x + 8 = 16/9
Subtract 8 from both sides:
x = -56/9
3 sqrt(x + 8) ⇒ 3 sqrt(8 - 56/9) = 4:
So this solution is incorrect
The solution is incorrect:
Answer: (no solutions)
3 sqrt(x + 8) = -4
Divide both sides by 3:
sqrt(x + 8) = -4/3
Raise both sides to the power of two:
x + 8 = 16/9
Subtract 8 from both sides:
x = -56/9
3 sqrt(x + 8) ⇒ 3 sqrt(8 - 56/9) = 4:
So this solution is incorrect
The solution is incorrect:
Answer: (no solutions)
Hello there!
[tex]3 \sqrt{x+8}=-4[/tex]
So this is the equation we have, and I'm guessing we have to solve for the value of x.
Let's divide both sides by 3.
[tex]\sqrt{x+8}=-4/3[/tex]
Square both sides to get rid of the square root.
[tex]x+8=(-4/3)^2[/tex]
[tex]x+8=16/9[/tex]
Subtract both sides by 8.
[tex]x=16/9-8=16/9-72/9=-56/9[/tex]
[tex]x=-56/9[/tex]
Let’s test if this is an extraneous solution by plugging this value into the equation.
[tex]3 \sqrt{-56/9+8}[/tex]
[tex]=4[/tex]
This does not produce the desired result, which was supposed to be -4. Thus, x=-56/9 is an extraneous solution, so there are no solutions to this equation.
I hope this helps and have an awesome day! :)
~AgentCozmo4, Moderator
[tex]3 \sqrt{x+8}=-4[/tex]
So this is the equation we have, and I'm guessing we have to solve for the value of x.
Let's divide both sides by 3.
[tex]\sqrt{x+8}=-4/3[/tex]
Square both sides to get rid of the square root.
[tex]x+8=(-4/3)^2[/tex]
[tex]x+8=16/9[/tex]
Subtract both sides by 8.
[tex]x=16/9-8=16/9-72/9=-56/9[/tex]
[tex]x=-56/9[/tex]
Let’s test if this is an extraneous solution by plugging this value into the equation.
[tex]3 \sqrt{-56/9+8}[/tex]
[tex]=4[/tex]
This does not produce the desired result, which was supposed to be -4. Thus, x=-56/9 is an extraneous solution, so there are no solutions to this equation.
I hope this helps and have an awesome day! :)
~AgentCozmo4, Moderator